OPTIMALISASI PENEGAKAN HUKUM PIDANA TERHADAP PELAKU PENCEMARAN LINGKUNGAN OLEH PERUSAHAAN INDUSTRI DI INDONESIA - Triadi, Triadi (Ensiklopedia of Journal, 2025)
Abstract: Criminal law enforcement against perpetrators of environmental pollution by industrial companies in Indonesia has experienced significant dynamics after the enactment of Law Number 11 of 2020 concerning Job Creation. This regulatory change brings a shift in the approach to law enforcement, where the principle of ultimum remedium is prioritized, so that administrative sanctions must be prioritized before criminal sanctions are imposed. Nevertheless, criminal law remains an important instrument to prosecute serious violations that cause serious environmental damage. The form of criminal law enforcement in this context includes the application of sanctions to individuals and corporations, with a focus on corporate criminal liability which is strengthened in regulatory changes. Criminal law enforcement must also pay attention to complex aspects of scientific evidence, the involvement of various institutions, and strengthening of monitoring and reporting mechanisms. The strategy for optimizing criminal law enforcement needs to be directed at several important aspects, including: strengthening technical evidence instruments, strict application of corporate accountability, synergy between law enforcement agencies, the effectiveness of implementing administrative sanctions, building an environmental legal culture, and sustainable policy reform. All of these strategies aim to maintain a balance between encouraging investment growth and ensuring environmental protection is maintained. With these optimization steps, it is hoped that criminal law enforcement can be more effective, provide a deterrent effect to perpetrators, and encourage industrial companies to be more responsible in managing the environmental impacts of their business activities.Keywords: Law Enforcement, Criminal, Pollution, Environment.